Trajetórias de exclusão e novas expectativas: um estudo sobre jovens e adultos em processo de alfabetização no município de Araraquara-SP - Pereira, Mônica (Universidade Federal de São Carlos, 2011)
The aim of this study is to show the school, family and professional trajectories that both young and adult students have followed during their years of schooling and literacy. In addition to this, we understand the reason to why school attendance drops during school age. Questionaires and interviews were applied and from this data we were able to understand the reasons that brought the students back to school and their new expectations towards education. The study was based on Pierre Bourdier´s theories, having as the main concepts, the habitus, cultural, economic and social capitals. It also describes a brief analyses of the education facilities provided in the city of Araraquara/SP and the characteristics of their literacy programme for both adults and young people (PROEAJA), the main literacy programme for local students. This programme aims to diminish the number of illiterate people around the city. This study also aims to find the expectations of the students and to analyse the internal and external factors that influence the students´ behaviour towards school. Last we describe a new area of poor school attendance due to the lack of quality inside the educational system.
Keywords: Alfabetização de adultos; Educação de jovens e adultos; Trajetórias escolares; Expectativas educacionais; Capital cultural; Habitus; Youth and adult education; School trajectories; Education expectations; Culture capital; Habitus; CIENCIAS HUMANAS::EDUCACAO